دراسة حول مفهوم القلاع (تاريخها - تصنيفها) - أديب أومري (Tishreen University, 2016)
إن أهم قضية في وجود الإنسان وبقائه هي الأمن والأمان، فجاء بناء القلاع كترجمة وانعكاس صادق لهذه القضية بكل تفاصيلها من جهة، وكمنتج تراكمي اجتمعت فيها الخبرات والتجارب وانصهرت فيها كل القيم لتشكل أهم معالم الحضارة العمرانية من جهة ثانية، بما قدمته من فن دفاعي كبير وذوق معماري رفيع. يتناول البحث دراسة لمفهوم القلاع مستعرضا المراحل التي مرت بها عمارتها عبر التاريخ، ثم شرحا عن تصنيفها وانواعها وأهميتها وأخيرا يرصد البعد الاجتماعي والجغرافي للقلعة ويخلص البحث إلى مجموعة من النتائج تؤسس لأبحاث لاحقة في المستقبل. The most important issue in human existence and survival is the safety and security, came to build castles as an expression and reflection honest to this issue in detail, on the one hand, the cumulative product met the experiences and melted in which all values of the most important urban civilization landmarks on the other hand, of its art defensive large, high architectural taste. This research deals with the study of the concept of castles reviewing phases of architecture throughout history, then an explanation for classification, types and importance and finally made the social and geographical dimension of the castle and concludes to establish a set of results for subsequent research in the future.